REVEALING PLEASURE THROUGH AMERICAN FICTIONS: NOSTALGIA FOR FANTASY FILMS - Rudy, Rudy (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2020)
American fantasy movies Lord of the Ring, Harry Potter, Pirates of Caribbean, and Narnia have become significant especially in the world of entertainment. They have attracted a lot of people around the world to watch. Therefore, it is interesting as well as essential to identify what kind of pleasure people get when they watch fantasy films and how this kind of genre may contribute to society. This study is theoretically useful to contribute to the development of theories in the relevant fields and practically help people to gain better understanding about fantasy films, especially for researchers, academicians, or students. Since films can be treated as symbols, theory of representation is used to show the meaning reflected from watching fantasy movies. The result indicates that fantasy films may offer pleasure such as escaping from the reality and evoking nostalgia which may be significant to understand the essence of life in American society.